Pertanggungjawaban Pidana terhadap Pencemaran Nama Baik melalui Media Sosial - Wahyuni, Sry; Yoserwan, Yoserwan (UNES Law Review, 2023)
This article explores the legal ramifications of defamation on social media as well as the types of behavior that fall under the heading of criminal defamation on social media. To make daily tasks easier for people to complete, technology is still being created. Internet-based criminal acts such as insults or defamation, perpetrated by one person against another person or organization, are becoming more common in Indonesia. The concept of error is one of the legality concepts used in the criminal responsibility system. Normative juridical research, which focuses on the application of constructive legal standards or principles, is the method used in this study. According to the findings of this study, Article 27 paragraph 3 of Law Number 11 of 2008 Concerning Electronic Information and Transactions and Article 45 paragraph 3 of Law Number 19 of 2016 Concerning Electronic Information and Transactions both govern how those who commit criminal acts of defamation through social media can be held legally accountable. Article 310 (1) of the Criminal Code governs the crime of slander. Basically, it happens when someone writes a post on Facebook with the intent to insult and libel the offender. Thus, the distribution of electronic material that involves insults or defamation is prohibited by Article 45 paragraph 3 of the ITE Law.